Activities and Learning Results of Islamic Education Through the Implementation of Cooperative Type Models Gallery Walk at Elementary School - Hanizon, Wirman; Fitriani, Fitriani; Helena, Helena (STIT Ahlussunnah Bukittinggi, 2022)
The condition of learning in elementary schools, especially Islamic Education currently still uses conventional learning models (lecture method). In learning, students only become objects, so it does not encourage students' potential to develop. PAI learning using the Cooperative Type Learning Model Gallery Walk in class V elementary school is very good to apply. This aims to ensure that students develop activity and creativity in the classroom, have an attitude of respect for other people and appreciate the work of others, learn to solve certain problems, learn to understand group diversity, and be able to socialize in group environments and social life. The approach used is the approach qualitative. Research data This is in the form of information about the process and data on the results of actions obtained from observations, interview results, and final tests. The data source is the process of implementing the Type Cooperative Learning Model Gallery Walk in learning Islamic Education in class V at Elementary School 09 Behind Balok Bukittinggi. The research subjects were teachers (observers), researchers (practitioners), and 26 class V students. Data analysis was carried out using a data analysis model. Research result shows that learning uses a cooperative learning model Gallery Walk is very well implemented to improve student learning outcomes. The research results obtained in the first cycle of the first meeting showed that student activity was 69.89%, in the second meeting it increased to 73.10%, and in the second cycle of the first meeting, it became 86.02%. Meanwhile, the learning outcomes in cycle I, meeting I, were 68.46%, meeting II was 76.15% and in cycle II, meeting I was 98.46%. This is proof of the success of the research carried out at elementary school 09 Behind Balok Bukittinggi.